Visualization of co-readership patterns from an online reference management system. Issue 1 (January 2015) - Kraker, Peter; Schlögl, Christian; Jack, Kris; Lindstaedt, Stefanie
<x xml:space="preserve">Abstract</x> Graphical abstract